Pelatihan Pembuatan Insektisida Herbal Minyak Sereh Bentuk Spray di RPTRA Jeruk Manis - Fitri, Dewi Rahma; Fajar, In Rahmi Fatria; Ekadipta, Ekadipta; Hardiyati, Iin (Jurnal Abdimas Jatibara, 2023)
The Real Work Lecture is one of the implementations of the Tridarma activities of higher education which includes community service activities. The theme of the activity is chosen based on the needs of the community. Cases of Dengue Hemorrhagic Fever (DHF) in Jakarta are still high, so prevention is carried out, one of which is by using simple and environmentally friendly herbal insecticides. This training activity was carried out to increase the knowledge and skills of the community about herbal insecticides. The activity begins with a pretest, delivery of material, training and ends with a posttest. The activity was attended by 20 representatives elected by the Kelurahan. Based on the results of the service, it was found that there was an increase in participants' knowledge about herbal insecticides as indicated by an increase in pretest to posttest scores, from 40% to 95%. The product after the training is in the form of herbal insecticide spray preparations that can be used by participants, and can be remade for use as home products.